Right to education in Afghanistan and the impact of the media - Marska, Małgorzata (Nawi, 2022)
Over the years scholars have researched how societies in conflict develop educational practices and examined the part education plays in creating or sustaining conflict. Afghanistan, due to its changing regimes and general uncertainty, is among the countries with the lowest rates of enrolment in modern education and of adult literacy. Given the 2021 developments, this article will focus on the legal obligations regarding the access to education, the history of the situation, the possible impact of current events, the positive role media can have when it comes to providing information to people living in conflict and the tangible impact the media has on the enrolment percentages.